Landscape Planning and Ecological Networks. Part B. A Rural System in Nuoro, Sardinia - Andrea De Montis; Maria Antonietta Bardi; Amedeo Ganciu; Antonio Ledda; Simone Caschili; Maurizio Mulas; Leonarda Dessena; Giuseppe Modica; Luigi Laudari; Carmelo Riccardo Fichera (TeMA: Journal of Land Use, Mobility and Environment, 2014)
This paper represents the continuation, i.e. Part B, of an homonymous paper aiming at designing an ecological network for the periurban area on the town of Nuoro in central Sardinia. While in Part A we illustrate the methodological premises and introduce a spatial network analysis-based study of a pilot ecological network, in this paper we apply a complex network analysis approach to the construction and characterization of the dynamics of the ecological network of Nuoro.  We are interested in monitoring the performance of the ecological network evolving from a real to a hypothetical scenario, where the two target vegetal species (holm oak and cultivated or wild olive) are present in each patch. We focus on global network properties and on three different centrality measures: degree, clustering coefficient, and betweenness centrality. We also take into account the influence of the intensity of the connection (i.e. the weight) by introducing the corresponding weighted centrality measures. Through thematic mapping we illustrate the pattern of each centrality indicator throughout the entire pilot set of patches. In this way, we demonstrate how spatial network analysis is useful to monitor the performance of the network and to support decision-making, management, and planning.